Mobile assets monitoring using RFID for UTAR Hospital - Ho, Huan Qian (2025)
Most of the service sectors like hospitality, education, banking, and other service sectors were manually entering the data of assets into the database. Sometimes, it causes data errors and inaccuracies since there are human typing errors or overlooking the number of lines of assets. Recently, AI and IoT are the most convenient technologies and are very useful in all sectors, especially in the service sector. They help sectors produce the most profit and productivity through technology. Since RFID is more convenient to use to check and update the data of assets, it is suitable for use in an asset monitoring system. The outcome of the project is a mobile application for the asset monitoring system using RFID for UTAR Hospital. The purpose of developing this mobile application is to keep track of the real-time incoming assets of the hospital. The assets will be labelled with RFID tags and registered using a mobile RFID reader, then the information of RFID tags will be uploaded to the server. In case of finding assets needed by hospital staff, they can immediately find the assets through the server and confirm the location of the asset. Area of Study: Java Programming, Networking Keywords: UTAR Hospital, Mobile Assets Monitoring, RFID, Frappe server, Assets tracking.